The effect of non-surgical periodontal therapy on glycemic control in Indian diabetics with periodontal disease – A systematic review and meta-analysis - Ghadge, Komal K.; Shetty, Sharath K.; Kulloli, Anita; Martande, Santosh; Mehta, Vini; Gopalakrishnan, D.; Mathur, Ankita; Fiorilla, Luca (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Periodontitis is a chronic inflammatory condition that contributes to systemic complications. It is associated with an increased risk of poor glycemic control and other diabetes-related complications. Purpose: This review aimed to evaluate the effect of nonsurgical periodontal therapy (NSPT) on the metabolic level of diabetes (HbA1c) in diabetic patients with generalized chronic periodontitis (GCP) in the Indian population. Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) criteria were followed for conducting the review. PubMed-MEDLINE, Cochrane Library, Scopus, and Google Scholar were searched from inception until January 30, 2025. The Cochrane risk of bias (ROB)-2 tool for randomized controlled trials (RCT) was used to assess quality. A p value of less than 0.05 was considered statistically significant, and the standardized mean difference (SMD) was employed as a summary statistic measure using a random effect model. Results: Eleven studies fulfilled the eligibility criteria and were included in the qualitative synthesis, of which only six studies were suitable for meta-analysis. The pooled estimate through the SMD signifies that periodontal therapy, or NSPT, had a significant reduction in the clinical parameters assessed (p < 0.05). Publication bias through the funnel plot showed symmetric distribution with the absence of systematic heterogeneity. Conclusion: This study highlights that NSPT as a standalone therapy significantly reduces metabolic markers, specifically HbA1c, in diabetic patients. Additionally, notable improvements in clinical parameters were observed following NSPT. Therefore, periodontal therapy should be considered for patients with elevated metabolic markers (HbA1c), as it may help to reduce both the inflammatory burden and HbA1c levels associated with diabetes.